Changes in the chemical composition of groundwater in Quaternary aquifer in Old Krakow, Poland (years 2002-2012) - Kasprzak, Agata; Motyka, Jacek; Wardas-Lasoń, Marta (Geology, Geophysics and Environment, 2013)
The chemical composition of the Quaternary aquifer in Old Krakow was studied. Thirty water samples were collected from wells in the years 2002, 2009 and 2012. The water chemistry of groundwater in Old Krakow is associated mainly with anthropogenic impact. The water samples represent manly five-ion type: Ca-Na-Cl-HCO3-SO4, Ca-Na-Cl-SO4-HCO3 and Ca-Na-HCO3-SO4-Cl, the multi-ion water type is typical for polluted water. The results of groundwater studies in Krakow between 2002 and 2012 showed that the chemical composition of water is being constantly affected by ancient human activities. The predominance of chloride and nitrate ions can be connected with a large number of the contamination sources. The main sources of contamination are accumulations of the anthropogenic soils and the cultural deposits containing organic, communal waste and sewage which were gathered in the oldest parts of Krakow.